KAJIAN SOSIOLOGIS TERHADAP LEGAL REASONING PEMBERLAKUAN NORMA KESOPANAN TERHADAP PELAKU TINDAK PIDANA DALAM PUTUSAN HAKIM DI INDONESIA - Eko Ari Wibowo (JURNAL SUMBER HUKUM, 2024)
Legal reasoning is basically an activity to look for the legal basis contained in a legal event, whether it is a legal act (agreement, trade transaction, etc.) or a case of legal violation (criminal, civil, or administrative) and include it in in existing legal regulations. In this case, legal reasoning in the application of politeness norms is one of the basic considerations of a judge in an effort to provide relief from criminal sanctions against the defendant. The research method used in this research is a normative method. The normative research method is a research method that focuses on library data. This type of research is a type of qualitative research with descriptive analysis. Juridically, politeness norms have been regulated in the provisions of Article 8 Paragraph (2) in Law Number 48 of 2009 concerning Judicial Power. Sociologically, legal reasoning in a judge's decision relating to norms of politeness can be manifested in the form of polite behavior by the defendant during the trial process. Keywords; Legal Reasoning, Criminal act, Judge's Decision.